Beyond WEIRD societies: Global social identifications across 45 countries and their socio-cultural and economic predictors - Samekin A. (Political Psychology. Volume47 Issue3, 2026)
In an increasingly globalized world challenged by multiple social problems, global social identifications (GSIs, e.g., with all humanity) are concepts of growing interest. Although such identifications can be affected by the cultural contexts in which they are manifested, research on them remains largely confined to Western, Educated, Industrialized, Rich, Democratic (WEIRD) societies. Using data collected in 45 countries (N = 9807, preregistered), we compared the strength of three types of GSIs between countries and cultural clusters, and explored the possible role of five cultural dimensions. The results revealed relatively small cross-national differences in GSIs overall, but African and South-East Asian cultural clusters reported significantly stronger identifications than those from other regions, with India, South Africa, and Ghana scoring the highest. Contrary to our hypotheses, GSIs were positively associated with in-group collectivism, survival values, and traditional values, while institutional collectivism was unrelated. As expected, humane orientation was positively related to most GSIs. Additional exploratory analyses showed higher GSIs in countries with a lower quality of life (broadly understood). GSIs were also more pronounced in less globalized, younger societies, with a higher proportion of men, fewer immigrants, and stronger diversity. Our study highlights the need to broaden research on GSIs beyond WEIRD contexts.
Keywords: all humanity; cultural clusters; global social identifications; globalization; quality of life